Efficient energy transfer and enhanced infrared emission in er-doped ZnO-SiO2 composites - Xiao, F. (2013)
Intense near-infrared (NIR) emission around 1534 nm has been obtained from ZnO-SiO2:Er3+ composites upon broadband ultraviolet light excitation. Remarkably, enhancement of the NIR emission as much as 20 times was achieved by optimal codoping with Li+ ions. To elucidate the relevant mechanisms, comprehensive spectroscopic measurements have been performed on ZnO-SiO2 composites with and without Er3+ ions doping. Photoluminescence spectroscopy and fluorescence decay dynamics clearly verify the efficient energy transfer from ZnO quantum dots (QDs) to Er3+ ions. Our results have not only demonstrated an efficient approach of color down-conversion but also indicated that ZnO-SiO2:Er3+ composites could be a promising material for optical amplifier using broadband UV pumping.